An Unprecedented Two‐Fold Nested Super‐Polyrotaxane: Sulfate‐Directed Hierarchical Polythreading Assembly of Uranyl Polyrotaxane Moieties. Issue 32 (8th July 2016) - Mei, Lei; Wu, Qun‐yan; Yuan, Li‐yong; Wang, Lin; An, Shu‐wen; Xie, Zhen‐ni; Hu, Kong‐qiu; Chai, Zhi‐fang; Burns, Peter C.; Shi, Wei‐qun
Abstract: The hierarchical assembly of well‐organized submoieties could lead to more complicated superstructures with intriguing properties. We describe herein an unprecedented polyrotaxane polythreading framework containing a two‐fold nested super‐polyrotaxane substructure, which was synthesized through a uranyl‐directed hierarchical polythreading assembly of one‐dimensional polyrotaxane chains and two‐dimensional polyrotaxane networks. This special assembly mode actually affords a new way of supramolecular chemistry instead of covalently linked bulky stoppers to construct stable interlocked rotaxane moieties. An investigation of the synthesis condition shows that sulfate can assume a vital role in mediating the formation of different uranyl species, especially the unique trinuclear uranyl moiety [(UO2 )3 O(OH)2 ] 2+, involving a notable bent [O=U=O] bond with a bond angle of 172.0(9)°. Detailed analysis of the coordination features, the thermal stability as well as a fluorescence, and electrochemical characterization demonstrate that the uniqueness of this super‐polyrotaxane structure is mainly closely related to the trinuclear uranyl moiety, which is confirmed by quantum chemical calculations. Abstract : More than radioactive : A uranyl‐based metal–organic rotaxane framework containing an unprecedented two‐fold nested super‐polyrotaxane substructure is prepared through sulfate‐directed hierarchical polythreading of 1D polyrotaxane chains and 2D polyrotaxane networks. This special assembly mode actually affords a new type of supramolecular chemistry instead of covalently linked bulky stoppers to construct a stable interlocked rotaxane moiety (see figure).